Draft literary work by Éamonn Ceannt entitled "Thought Transference and Stage Illusions" refering to magic tricks and street preformers - Ceannt, Éamonn, 1881-1916
Includes corrections and an annotation " 47 Reuben Avenue Dolphin's Barn".
Keywords: Ireland -- History -- 20th century